Unseen tragedies: analysing accidental deaths in India - Pradhan, Saumyasree; Kund, Nitushree; Hota, Rabindra Nath; Goswami, Shreerup (International Journal of Public Health Science (IJPHS), 2025)
Traffic accidents represent a critical public health and socio-economic issue in India. This manuscript examines the critical issue of accidental deaths due to traffic incidents in India, highlighting the alarming trends and underlying factors contributing to rising fatalities. The analysis employs bivariate and multivariate statistical methods, including correlation, time series analysis, multivariate factor and cluster analyses, to explore the relationships between accident severity, fatalities, and injuries. Key findings include significant positive correlations between the year and death rates, as well as between accident severity and fatalities, indicating a persistent increase in road traffic deaths over time. Notably, the severity of accidents is directly linked to higher fatality rates. The analysis identifies two primary clusters: i) time (year) severity and death, and ii) accidents and injuries. The results underscore the need for effective interventions, including improved infrastructure for non-motorized transport, enhanced road safety measures, and stricter enforcement of traffic regulations. By promoting shifts from car travel to cycling and walking, the study advocates for sustainable transportation solutions to mitigate the growing toll of road traffic accidents in India.